Famines between celestial pests and human factors in Algeria - from the early 18th century to the first third of the 19th century- - Masoudi, Fatiha; bin Atto, Hamdoun; Laid, Fares (The Algerian Historical Journal, 2026)
In this paper, we discuss the economic and social topic of Algeria in the Ottoman era, and as a historical study of part of the pandemics and crises that affected the country in this period, we touched on the famines that algeria was repeatedly subjected to, which was often part of a series of events experienced by the state, as a disaster that ruined the demographic growth of the population of Algeria, regardless of the natural and human factors behind it, after which it was known a series of major transformations and decisive turns in its historical course, which often prevented Without accelerating development, it is characterized by the breakdown or lack of food security as a result of a number of causes, including direct and indirect causes, and has strong security, psychological and social impacts.